Inflammatory skin diseases and the risk of chronic kidney disease: population‐based case–control and cohort analyses. (1st October 2021) - Schonmann, Y.; Mansfield, K.E.; Mulick, A.; Roberts, A.; Smeeth, L.; Langan, S.M.; Nitsch, D.
Summary: Background: Emerging evidence suggests an association between common inflammatory skin diseases and chronic kidney disease (CKD). Objectives: To explore the association between CKD stages 3–5 (CKD3–5) and atopic eczema, psoriasis, rosacea and hidradenitis suppurativa. Methods: We undertook two complementary analyses; a prevalent case–control study and a cohort study using routinely collected primary care data [UK Clinical Practice Research Datalink (CPRD)]. We matched individuals with CKD3–5 in CPRD in March 2018 with up to five individuals without CKD for general practitioner practice, age and sex. We compared the prevalence of CKD3–5 among individuals with and without each inflammatory skin disease. We included individuals in CPRD with diabetes mellitus (2004–2018) in a cohort analysis to compare the incidence of CKD3–5 among people with and without atopic eczema and psoriasis. Results: Our study included 56 602 cases with CKD3–5 and 268 305 controls. Cases were more likely than controls to have a history of atopic eczema [odds ratio (OR) 1·14, 99% confidence interval (CI) 1·11–1·17], psoriasis (OR 1·13, 99% CI 1·08–1·19) or hidradenitis suppurativa (OR 1·49, 99% CI 1·19–1·85), but were slightly less likely to have been diagnosed with rosacea (OR 0·92, 99% CI 0·87–0·97), after adjusting for age, sex, practice (matching factors), index of multiple deprivation, diabetes, smoking, harmful alcohol use and obesity. Results remained similar after adjusting for hypertension and cardiovascular disease. In the cohort with diabetes ( N = 335 827), there was no evidence that CKD3–5 incidence was associated with atopic eczema or psoriasis. Conclusions: Atopic eczema, psoriasis and hidradenitis suppurativa are weakly associated with CKD3–5. Future research is needed to elucidate potential mechanisms and the clinical significance of our findings.